Interactions of amino terminal domains of Shaker K channels with a pore blocking site studied with synthetic peptides. - Ruth D. Murrell‐Lagnado; Richard W. Aldrich (1993)
Synthetic peptides of the five alternative NH2-terminal sequences of Shaker when applied to the cytoplasmic side of ShB channels that have an NH2-terminal deletion (ShB delta 6-46) block the channel with potencies correlated with the rate of inactivation in the corresponding variant. These peptides share no sequence similarity and yet three out of the five have apparent dissociation constants between 2 and 15 microM, suggesting that the specificity requirements for binding are low. To identify the primary structural determinants required for effective block of ShB delta 6-46, we examined the effects of substitutions made to the 20 residue ShB peptide on association and dissociation rates. Nonpolar residues within the peptide appear to be important in stabilizing the binding through hydrophobic interactions. Substitutions to leucine-7 showed there was a clear correlation between hydrophobicity and the dissociation rate constant (koff) with little effect on the association rate constant (kon). Substituting charged residues for hydrophobic residues within the region 4-8 disrupted binding. Within the COOH-terminal half of the peptide, substitutions that increased the net positive charge increased kon with relatively small changes in koff, suggesting the involvement of long-range electrostatic interactions in increasing the effective concentration of the peptide. Neutralizing charged residues produced small changes in koff. Charges within the region 12-20 act equivalently; alterations which conserved net charge produced little effect on either kon or koff. The results are consistent with this region of the peptide having an extended conformation and suggest that when bound this region makes few contacts with the channel protein and remains relatively unconstrained. Analogous mutations within the NH2-terminal domain of the intact ShB channel produced qualitatively similar effects on blocking and unblocking rates.